Strategic evaluation of rural-to-urban migration trends and policies in Türkiye - Sukran Seker; Ertugrul Ayyildiz; Nezir Aydin (Sustainable Futures)
Rural-urban migration refers to the movement of people from rural to urban areas. This study strategically evaluates rural-to-urban migration trends and policies in Türkiye using Multi-Criteria Decision-Making (MCDM) methods under Fermatean fuzzy logic. The main and sub-factors influencing rural-to-urban are identified and structured under the PESTELT (Political, Economic, Social, Technological, Environmental, Legal, and Transportation) framework. It identifies key drivers of rural-to-urban migration, such as employment opportunities and educational access, rather than solely focusing on the cost of living. The goal is to develop strategies that encourage reverse migration back to rural areas. Using integrated Fermatean Fuzzy-Analytical Hierarchy Process (FF-AHP) and Fermatean Fuzzy-Evaluation based on Distance from Average Solution (FF-EDAS) methods, the study prioritizes strategies like regional employment investments and promoting village industries to strengthen rural settlement. Findings offer policy insights to balance urban-rural population distribution sustainably.